Prevalence and factors associated with traumatic dental injuries among grades 5 and 6 pupils in private and public elementary schools in manila - Dizon, Kristine M.; Vibar, Mary Abigail H.; Meneses, Michelle Marie Z. (Co-author).; Gener, Ria (Adviser).
The prevalence of traumatic dental injuries (TDI) among school children in different countries has been reported to range from 6% to 29.6%. These figures underestimate the occurence of TDI because minor TDI's are underreported. In the Philippines, the prevalence of TDI in filipino children has not been well-documented. The study aims to assess the prevalence and associated factors of dental traumatic injuries of permanent incisors of 5th and 6th grade school children in public and private schools located in 5th district of Manila. Methods: A dental trauma cross-sectional study through clinical examination of upper and lower incisors and surveys with 327 grades 5 and 6 school children enrolled in public and private schools were carried out by two dental clinicians. TDI were classified according of the WHO classification. Frequency distribution and cross tabulation were used for data analysis. Results: The prevalence of dental injury was 24.8% (95% CI). There is a statistical difference between the prevalence of boys and girls (p=0.026). The maxillary incisors were the most affected teeth (70.7%). Single tooth injury was predominant in all age groups. The presence of incisal overjet and anterior openbite and child's age has no statistically significant association with TDI. Enamel fracture (77.3%) was the most common type of dental trauma and was mainly due to falls (36%) and biting on hard objects (20%). The majority of TDI occurred at home (68%). Results also showed that socioeconomic factors has no statistically significant association with TDI. Conclusion: The prevalence of TDI in selected private and public schools in Manila is slightly higher compared to other studies. Thus, prevention, management and treatment of TDI should be emphasized to the public, the health professional and policy makers. Future investigations into the relationship of TDI and other related factors are indicated.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.